Collecting Medieval and Renaissance Manuscripts in Twentieth-Century Great Britain and North America. Issue 1 (1st July 2019) - Burrows, Toby
Abstract : Medieval and Renaissance manuscripts were a significant commodity in the antiquarian sales market throughout the twentieth century, sought out by very wealthy collectors and small-scale buyers. The history of this manuscript market has not been analyzed systematically. This article is a first attempt to identify themes and trends across the century, beginning with the dominance of the great American Gilded Age collectors like Henry Huntington and the Morgans and their need to memorialize themselves. It argues that future research needs to assemble comprehensive data on prices and buyers in order to make possible more systematic analyses of trends and activities, and a more sophisticated understanding of the different reasons for which collectors collected and of the changing nature of manuscripts as objects with their own biographical trajectories and their own agency.